(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2026)
Nowadays, terminology has become a central subject of scholarly inquiry due to the rapid development of this field within linguistics. Ongoing processes such as the creation of new lexical units, semantic shifts in existing words, lexicalization phenomena, the formation of stable multiword expressions, and lexical borrowing across languages have intensified academic interest in terminological studies. Terminology is viewed not only as a subfield of linguistics but also as an interdisciplinary domain connected to sociology, cognitive science, philosophy, and related disciplines. As a scientific field, terminology examines the identification, definition, formation, and systematization of lexical units—specifically terms—associated with particular areas of knowledge across different languages. This article emphasizes the role of terminology as a fundamental component of linguistic theory and practice.